Clinical markers of slow healing and relapsing gastric ulcer. Issue 2 (February 1987) - Battaglia, G; Di Mario, F; Piccoli, A; Vianello, F; Farinati, F; Naccarato, R
Abstract : The aim of the study was to identify the clinical markers useful in characterising slow healing and relapsing gastric ulcer patients. Ninety nine subjects entered the short term and 79 the long term study (12 months). The following parameters were taken into account: therapy, sex, age, smoking habit, alcohol consumption, analgesic intake, peptic ulcer family history and onset of the disease. Results of the studies were analysed by means of chi 2 test and logistic regression, both in stepwise and in specifying models. Cigarette smoking was found to be the most important risk factor of non-healing (p = 0.04). In women with late onset of the disease, cigarette smoking identified the gastric ulcer subjects at higher risk of non-healing with a predictive probability of 0.4679. Age under 50 years was found to be the most important risk factor of relapsing throughout the entire 12 month follow up period (p = 0.025). In those under 50 years, cigarette smoking and negative peptic ulcer family history in combination, identified the gastric ulcer subjects at higher risk of relapsing, the predicted probability being 0.6027. It is concluded that cigarette smoking is the most important risk factor for non-healing and those who relapse under the age of 50. The possibility of singling out categories of patients more prone not to heal and to relapse suggests new strategies in the management of gastric ulcer disease.